Characteristic Test of AC - WC Mixture Using Tambolang Rock, North Toraja Regency - Merdi Indra Asrinto; Alpius; Sufiati Bestari (Program Studi Teknik Sipil UKI Paulus-Makassar, 2021)
Material testing was carried out to obtain the characteristic value of the AC-WC mixture using the TamboIang mountain rock aggregate. The methods used are testing coarse aggregate, fine aggregate, filler, aspaI with the composition design of the aspaI content for AC-WC and then testing conventional marshaII as a determinant of the optimum asphalt content, after which the KAO specimen is made to obtain Remaining MarshaII Stability (SMS). The results of the aggregate characteristic test from the Tambolang mountain rock, North Toraja Regency have met the general specifications of Bina Marga as an AC-WC mixture where conventional marshaII testing with asphaIt content is 5.5%,6.0%, 6.5%, 7.0% , 7.5% and the resuIts of the MarshaII immersion test with KAO for AC-WC is 7.5% with the remaining MarshaII Stability (SMS) value of 96.52%. From the resuIts of this test, it can be concIuded that the aggregate from Mount Tambolang, has met the General Bina Marga Specifications 2018.